Distributed Leadership: A Bibliometric Analysis Using Scopus Database (1981-2020) - García-Carreño I.V. (The European Educational Researcher, 2021)
Distributed Leadership is a conceptual and analytical approach to understanding leadership that is focused on interactions between leaders and those they lead with the goal of driving instructional improvement and improving student outcomes by developing high-quality teaching and an educational culture that enables all students to thrive. This article provides an overview of the state-of-the-art research available on distributed leadership. As new social and educational demands emerge, leadership responses need to be reformed at all school levels to ensure a school’s ability to provide a high-quality education. These transformations must be promoted from within each school center. The author describes and covers a deep review of the literature between 1981 and 2020. The source data for this research, (321 articles), is derived from SCOPUS, Biblometrix Studio, and VOSviewer. The terms and their clusters were illustrated on graphs, and density maps were utilized. General recommendations are provided and challenges are identified for the incorporation of DL changes into the management of schools. The findings show that the literature refers explicitly to DL, wherein there are a number of interesting insights provided by theoretical articles. A conclusion is given with recommendations for further multidisciplinary research at the intersection of the fields in order to show the holistic landscape of this field.